Extensão popular: debatendo autonomia e participação em hortas urbanas no PINAB/UFPB - Botelho, Bruno Oliveira de (2017)
The present study came to be with reflections and questionings that came together along with eight years of working and experimenting Extension in the light of Popular Education within the university, especially with the Program of Integral Practices of Health Promotion and Nutrition in Basic Attention (PINAB) and it’s fronts with Food and Nutrition Security and Combating Hunger and Poverty through urban and community gardens. From 2013 to 2015, PINAB developed the Community Garden Boa Esperança and from 2016 to this day, the Community Garden Horta no Vila. It saught with these initiatives the appreciation of a direct interaction with nature, strong for basic health care that brings the counterpart to environmental depredation and the impersonality of each individual in this process, seeking out to reflect upon sustaintability e new ways of thinking our political and economical context. Popular Extension in university has its challenges: it comes with, supports and inspires actions of social transformation. The educational process with it comes with changing behavior patterns, attitudes and ways of living. As we question the reaches that this social transformation may have as part of a modern hegemonic pattern stabilished, as well as which aspects of Popular Extension could exercise its counter hegemonic role, we came out to two categories. The main objective of this study is to analyze Popular Extension and it’s relation with the categories Authonomy and Popular Participation through the experience of urban gardens in PINAB, from the involved subjects’s point of view. To make this qualitative and exploratory study happen, we opted to agree with the dialectical method through content analysis of semi-structured interviews, documents, bibliographic references and personal observations. In the involvement with Urban Agriculture and Popular Education, students, public health users and public health professionals could get together and realize the start of collective products results. We comprehended with this study that Popular Paticipation can promote learnigns capable of actions that converge main elements of Authonomy. This comprehension shed its light in Popular Education as, in practice, Popular Extension will hardly compose emancipatory actions, the full extent of Authonomy will not come as a messianic gift to be delivered in the lap of subalternized people. Although, Popular Extention has been consistently capable of exercising everyday new ways of interactions and these ways could be capable of pointing ways to full extent of Authonomy that will only be effective if participative.